Sesamolinol glucoside, disaminyl ether, and other lignans from sesame seeds - Grougnet, R.a; Magiatis, P.b; Laborie, H.b; Lazarou, D.c; Papadopoulos, A.c; Skaltsounis, A.-L.b (Journal of Agricultural and Food Chemistry, 2012)
The application of a procedure based on XAD-4 adsorption resin permitted the obtainment of an enriched polyphenolic extract from Sesamum indicum seeds. Chemical analysis of the obtained extract led to the identification of 12 lignans. Among them, 2 lignans, (+)-sesamolinol-4'-O-β-d-glucoside and disaminyl ether, are reported for the first time as natural compounds. Their structure has been determined by spectroscopic methods, mainly by the application of one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) techniques [heteronuclear multiple-quantum coherence (HMQC), heteronuclear multiple-bond correlation (HMBC), and nuclear Overhauser effect spectrometry (NOESY)] and mass spectroscopy. The isolated compounds were evaluated for their antimutagenic activity. Among the tested lignans, the most active lignan was found to be sesamolin, followed by sesamolinol and samin, against H2O2. Additionally, some of the tested lignans showed desmutagenic activity against benzo[a]pyrene (BaP). © 2011 American Chemical Society.
cited By (since 1996)2
Keywords: Adsorption; Antimutagenic activity; article; Benzo[a]pyrene; chemistry; Ethers; glucoside; Glucosides; Heteronuclear; Isolated compounds; lignan; lignans; mass spectrometry; Mass spectroscopy; Multiple-quantum coherences; Natural compounds; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Nuclear magnetic resonance techniques; Nuclear overhauser effect spectrometries; plant extract; Plant Extracts; plant seed; Quantum theory; Resins; Seeds; sesamolinol diglucoside; Sesamum; Sesamum indicum; Spectroscopic analysis; Spectroscopic method; XAD-4 resin adsorption